The Effect of Using Educational Digital Images in Learning Simple Arithmetic Operations and Conveying The Learning Effect among Students with Intellectual Disabilities - Hakami, Maqbul Mohammed; Al-Shehri, Ali Mohammed (Journal of Educational and Psychological Sciences, 2025)
The study aimed to examine the impact of using educational digital images on learning basic arithmetic operations and the transfer of learning among educable intellectually disabled students in the Jazan region. The researcher employed an experimental approach using a quasi-experimental design based on a single group with pre- and post-testing. The research tool consisted of multiple-choice questions, applied to a sample of 10 students from the Institute of Intellectual Education in Al-Hasmah. The results revealed statistically significant differences between the pre-test and post-test scores for addition and subtraction, indicating the effectiveness of digital images in improving the learning of basic arithmetic operations. Moreover, no statistically significant differences were found between the post-test and the delayed test, suggesting the sustained impact of learning. Based on the findings, the researcher recommended the use of educational digital images in teaching students with intellectual disabilities and encouraged the use of the current study tools in future research. Additionally, the study proposed conducting further research to apply these tools to more advanced arithmetic operations, female students with intellectual disabilities, typically developing students, and other academic subjects.